PELATIHAN BUDIDAYA JAMUR TIRAM SEBAGAI PROGRAM PENGEMBANGAN KEWIRAUSAHAAN DI SMA ISLAM ROUDLOTUN5 NASYIIN BERATKULON – MOJOKERTO - Dinaloni, Diah; Muktiadji, Henky; Riva, Hastin (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The existence of the high school level is increasingly being replaced by the presence of the vocational school level. This is because most people think that high school graduates are not ready to work and are not independent. So, one of the efforts made is through training in oyster mushroom cultivation. Oyster mushroom cultivation training was chosen because it does not require too much land, is easy to maintain, and is not too expensive. What is even more supportive is that the materials used to develop oyster mushroom cultivation are widely available in Beratkulon Village, Kemlagi District, Mojokerto Regency. In Beratkulon Village, many people work as builders, especially frame makers, so in Beratkulon Village there is a lot of wood sawdust that is not used by the residents. Wood is the main medium for growing oyster mushrooms in nature, so wood sawdust is very suitable as a cultivation medium. In Beratkulon Village there is also a huller (rice mill) so it is very easy to get bran which is an additional ingredient for making oyster mushroom baglog. The fine bran (rice bran) in the mushroom medium functions as a source of carbohydrates and minerals for the mushroom. The aim of Community Service is that it is hoped that Roudlotun Nasyiin Islamic High School students will be able to become entrepreneurs by opening their own business opportunities so that they are expected to be able to accommodate community needs, build abilities in increasing income, carry out business-scale businesses and develop participatory planning and implementation of activities. The training targets were students at Roudlotun Nasyiin Islamic High School, Beratkulon Village, Kemlagi District, Mojokerto Regency. The methods and approaches used in this training activity are discussion and practice. The result of the oyster mushroom cultivation training activity was an increase in students' understanding and skills in oyster mushroom cultivation. The conclusion that can be drawn is that creating your own job opportunities at Roudlotun Nasyiin Islamic High School can be done by developing entrepreneurship in the form of training in oyster mushroom cultivation by utilizing local potential in the form of sawdust and fine bran (rice bran) which so far have not been utilized by residents. Because this oyster mushroom cultivation training has a positive impact so that it can later be utilized as a business opportunity by students at Roudlotun Nasyiin Islamic High School, the oyster mushroom cultivation training needs to be continued and facilitated by the school in the context of developing entrepreneurship, so that students are expected to be entrepreneurial and independent. economically